Semantics and Functioning of Color Terminology in Autobiographies of Artists from Late 19th to Early 20th Century - M. M. Sandalova; L. V. Kalinina (Научный диалог, 2025)
This article provides a comprehensive review and analysis of the instances of color terminology used in the discourse of artists as professionals engaged with color. The aim of this research is to uncover the specific features of color perception and verbalization, as well as the employment of color names in the language of artists. The study is based on 2,500 contexts selected from the autobiographies of notable figures such as Marc Chagall, Konstantin Korovin, Kuzma Petrov-Vodkin, Ilya Repin, and Nicholas Roerich. Employing methods from structural analysis (component analysis, distributional analysis, semantic field analysis), cognitive semantics (cognitive interpretation method), and psycholinguistics (experiments, surveys), the paper presents general statistics on the usage of color names within the analyzed material. A categorization of color terminology is proposed based on cognitive foundations, corresponding to the type and level of mental distortion of color in relation to objective reality. The analysis addresses color names in the context of artists’ speech, examining their use as both painters and art philosophers. The role of generic terms kraska [paint] in reflecting the material embodiment of color is also discussed. Additionally, the study raises questions regarding the use of prototypical combinations (e.g., zelenyy lug [green meadow]). It is established that artists conceptualize color names as independent phenomena, subjects of discussion and evaluation, aiming for precision in expression over vividness, and tending to utilize professional terminology while imbuing color names with additional evaluative qualities.